A one-arm pilot trial of a telehealth CBT-based group intervention targeting transdiagnostic risk for emotional distress. - Sierra Flynt; Grace Y Cho; Brandon Koscinski; Catherine Accorso; Ashley Knapp; Stephanie Gorka; Julie Suhr; Megan Austin; Nicholas P Allan (PLoS ONE)
The COVID-19 pandemic had a significant impact on mental health, straining an already overburdened healthcare system and highlighting health inequity issues. To streamline treatment efforts, targeting transdiagnostic risk factors for symptoms of emotional distress through a modular, transdiagnostic approach via telehealth may help to expand access to mental health treatment. Three transdiagnostic risk factors for emotional distress disorders that emerged as important treatment targets during the pandemic are anxiety sensitivity (AS) (i.e., fear of anxious arousal), intolerance of uncertainty (IU) (i.e., distress when confronted with uncertainty), and loneliness. To target AS, IU, and loneliness, we completed a pilot feasibility, acceptability, and utility trial of Coping Crew, our group, telehealth-delivered transdiagnostic treatment protocol. The 17 participants (Mage = 22.00, SD = 4.46; 71% female) rated the intervention and study protocol as feasible to deliver and acceptable and useful to address intervention targets. Evidence was mixed regarding feasibility, acceptability, and usefulness of the mobile app: 94% of the participants (n = 16) completed at least one daily survey 80% of the time, but only 35% of the participants (n = 6) completed at least 80% of the mobile app surveys over the course of the intervention. Most participants rated use of the app as acceptable and relevant to psychological improvements made due to the intervention. Exploratory analyses suggest potential reductions in transdiagnostic risk factors at post-intervention, which were maintained at 1- and 3-month follow-up. Detailed effect size estimates are provided. However, these should be interpreted with caution due to the small sample size and exploratory nature of the study.